Efektifitas Problem-based Learning dengan Brainwriting berbasis Masalah Diversifikasi Pangan terhadap Kemampuan Berpikir Kritis dan Berkomunikasi Siswa - Iis Aprilia Arsanti; Agung Wijaya Subiantoro (Jurnal Pendidikan Biologi, 2020)
This research aimed to examine the effectiveness of the implementation of Problem-based Learning with brainwriting method based on food diversification problem toward students’ critical thinking and communication skills. This was a quasi-experimental research using a non-equivalent pretest-posttest control group design, which involved two classes of 10th-grade student that selected by cluster random sampling, in a public high school at Bantul regency, Special Region of Yogyakarta. One class was managed as the experimental group, and another one was as the control group. The data of critical thinking skill were collected using an essay test instrument which analyzed using the Mann-Whitney U test, while communication skill data were collected through an observation protocol and analyzed descriptively. The findings of this research revealed that the Problem-based Learning instruction with brainwriting method was significantly more effective in developing students’ critical thinking and communication skills, as Mann-Whitney U test supported this result (p=0.00) as well as the descriptive analysis of the average scores of the skills. With this significance, Problem-based learning with the brainwriting method can be used as an example of a model and enrich the learning model implemented by teachers. These results are further discussed in this paper.